KEBIJAKAN PEMERINTAH DAERAH DALAM MENERAPKAN DESENTRALISASI FISKAL MELALUI PENERIMAAN PAJAK BPHTB KOTA DUMAI TAHUN 2017/2018 - Rizki Aji Sasongko; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Fiscal policy is a policy of adjustment in the field of spending and receipts to improve the state of the economy. Economic policy is expected to lead to better economic conditions by changing government revenue and spending. The implementation of fiscal decentralization policies should provide changes in the financial structure of the region. According to the results of pre-observation of researchers in dumai people who pay BPHTB tax, there are some obstacles found in the field among them there are domiciled communities that do not report so this makes it difficult for officers to process the verification of BPHTB tax data in Dumai City.          This research aims to find out the Local Government Policy in Implementing Fiscal Decentralization Through The Tax Receipt of BPHTB Dumai City In 2017/2018 and To see what factors are a block in the Local Government Policy in Implementing Fiscal Decentralization Through Tax Receipts bphtb Dumai City Year 2017/2018. The research approach used in this study is a qualitative approach to informant selection techniques in this study that uses purposive sampling techniques. Data collection techniques are by interview method and written notes.          The results of the study found the Local Government Policy in Implementing Fiscal Decentralization through the Tax Receipt of BPHTB Dumai City Year 2017/2018 has not been optimal. There are four factors blocking local government policy in implementing fiscal decentralization through the receipt of bphtb tax dumai city in 2017/2018 namely: Centralization of Taxation, Researchers found a discrepancy between the content of existing policies and the policies implemented. Participation of BUMD, the fiscal decentralization imbalance that occurs in Dumai City also occurs due to the lack of role of BUMD as a source of regional income. Competition Tax, One of the low tax receipts in Dumai City is The Acquisition Duty ha katas Land and Buildings. Regional Expenditure Allocation, Regional Revenue and Expenditure Allocation (APBD) dumai city in 2017 experienced deficit, several factors including the entry of balancing funds and other receipts from the central government to the region. Key Words: Fiscal Decentralization, Policy, Taxation.